Current Trends in the Russian Financial System - Stephan Barisitz; Zeljko Bogetic; Zuzana Fungacova; Laura Solanko; Peter Havlik; Valery Invushin; Vladimir V. Osakovsky; Debora Revoltella; Alexander Lehmann; Ewald Nowotny; Cyril Pineau-Valencienne; Pekka Sutela (SUERF - The European Money and Finance Forum, 2009)
The papers in the present SUERF Study is a selection of the papers presented at a SUERF Workshop and Special OeNB East Jour Fixe held at Oesterreichische Nationalbank in Vienna on 23 January 2009. In his opening remarks (chapter 2), Ewald Nowotny, Governor of the Oesterreichische Nationalbank referred to Austrian banks? engagement with neighbouring Central and Eastern European Countries. The current crisis should not make people forget the fact that Austrian banks? deep engagement with the neighbouring countries is one of the success stories in Austrian economic history. Since the fall of the Berlin Wall, Austrian banks have become one of the driving forces of the process of structural adjustment, modernization of business practices, and deepening of financial intermediation in the region. At end 2007, in Central Europe, the share of Austrian banks surpassed a fifth of aggregate sector assets, in Southeastern Europe even a third of the respective total. A considerable share of the earnings of Austrian banks comes from banking activities in Central and Eastern Europe. Austrian bankers can claim to be among the pioneer foreign investors in Russia, Ukraine, Kazakstan and Belarus. The international financial crisis has from September 2008 demonstrated Russia?s structural vulnerability. The comprehensive countermeasures by the Russian authorities to assist the banking sector and the economy are characterized by the Governor as worthy endeavours. Chapter 3 is based on the keynote speech by Pekka Sutela, BOFIT, Bank of Finland ?Russian Finance: Drag or Booster for Future Growth?? The author praises the Russian authorities for having made prudent decisions in recent years. The Putin-Kudrin regime chose a stability-oriented macro policy. The very strong increase in the global oil price up to 2008 implied a strong growth in the value of Russian exports and lead to an impressive GDP growth. The author uses the term ?windfall?. The Russian Government decided to pay back practically all foreign debt, much of it ahead of schedule. The regime wanted to bring back what they see as Russian sovereignty and in particular to avoid being dependent on IMF or other foreign financiers. Their policy contributed strongly to an improvement of Russia?s general credit-worthiness and to a growth in foreign reserves. During the 1990s, lack of trust in the rouble had as consequence that the US dollar was applied to a considerable extent in payments between Russians. The stability oriented policy after 2001 contributed to a de-dollarization of the economy up to 2008. It follows from the stability-oriented policy that Russia was relatively well prepared when it was hit by the global financial crisis in 2007?2008. In the autumn of 2008, however, the general public started to withdraw bank deposits and the relative share of foreign exchange deposits increased again. The public shifted towards foreign currency cash assets. The author explains that Russia has a dual economy. The natural resource based sectors are clearly globally competitive but the sectors outside the resource sectors are not. The big resource based companies have relied on foreign markets for their financial needs. The home market is primarily serviced by domestic banks. At the end of September 2008, government-controlled banks had 47.8% of all bank assets. The state maintains banking sector stability primarily through state banks. The author?s answer to the question in the headline is: ?The Russian financial system is rather a drag than a booster for future growth?. In addition, it is unlikely that Russia will become a regional financial centre or an inventionbased society in the foreseeable future. Chapter 4 by Stephan Barisitz, Oesterreichische Nationalbank, is ?Russian Banking in Recent Years: Gaining Depth in a Fragile Environment.? The author shows tables with macroeconomic, monetary and financial indicators for Russia for the years 2002?2008. Key observations are: Strong economic growth, strong dependence on oil prices, inflation problems, recent volatility of private capital in- and outflows. Banking development initially featured rather slow recovery from the financial crisis of 1998, coupled with sluggish reforms. This was followed by a stepped-up pace of institutional and structural adjustments in 2003?2005, which brought about major improvements of banking activities and of the regulatory framework. The return on equity (ROE) of banks was in 2006?2007 above 20%. The solvency ratio of banks declined steadily up to 2008 due to strong growth in bank assets. The oil price driven improvements in Russia?s terms of trade over the period 1998 to 2008 combined with political stability, prudent macroeconomic policies and some successful institutional and structural reforms have supported Russian economic expansion. Not only exports, but also consumption, have driven strong GDP growth. Financial intermediation continued to deepen swiftly in Russia up to the fall of 2008, despite important repercussions of the US subprime crisis. As the interbank market tightened during 2008 and capital outflows increased, Central Bank of Russia reacted quickly with repeated liquidity interventions. Following the continuous oil price decline and pressures on the rouble, Central Bank of Russia intervened extensively in the foreign exchange market and draw down foreign exchange reserves. The controlled depreciation strategy initiated in November 20078 has not stopped the decline in foreign exchange reserves. Due to the still sizable foreign reserves, the relatively high profitability of banking activity and the satisfactory capital adequacy level as shock absorbing factors, Russia seems to be in a better position to handle the financial crisis than many other countries. Chapter 5 by Alexander Lehmann, European Bank for Reconstruction and Development has the headline ?Banks and Financial Reform: Their Role in Sustaining Russia?s Growth.? The paper focuses on the strength of the link between economic growth and financial development. Even in East European transition countries where a positive correlation between finance and growth developed in the 1990s, there was little microeconomic evidence that the financial sector actively supported growth. Investments were overwhelmingly financed through retained earnings, and what little external finance was raised came from foreign direct investment. Around year 2000, this changed. Regulatory improvements, better enforcement and rapid development of individual institutions meant that the financial sector undoubtedly has supported economic growth since year 2000. The disruption to credit growth since 2008 and the simultaneous downturn of the Russian real economy has made the link abundantly clear. EBRD evaluates the progress in structural reforms in transition countries by means of ?transition scores?. The author shows an exhibit which illustrates the development of the EBRD transition score for Russia from 1989 to 2006. It shows that the fastest progress took place from 1995 to 2003. The improvements in the regulatory framework for banking activity supported financial intermediation and Russian banks expanded their balance sheets and diversified into lending to retail customers and SMEs. For corporate investment as a whole, however, the share of new investment financed through bank credit remained relatively small. The sectors that saw sharp increases in investment and accounted for the bulk of capital spending, predominantly benefited from internal cash flows, or benefited from public support or ownership. Chapter 6 by Cyril Pineau-Valencienne, CEO, CPV Conseil, is ?Russian financial institutions and the oil and gas sector: funding and recycling.? The paper first outlines the importance of the oil and gas sector for the Russian economy. Capital expenditures in the sector grew strongly from 1999 to 2007. The huge investments were to a large extent financed by internal operating cash flows and by borrowing in international financial markets. The big oil and gas companies are important customers for foreign banks. The companies also have their own so-called raw material banks but these banks have not played a major role as related parties in the financing of the investments of these groups. The willingness of the oil and gas companies to incur debt denominated in foreign currency must be understood in the light of their revenue structure. Contracts in the global energy markets are primarily denominated in US-dollars and the companies are therefore to a considerable extent able to match currency revenues from exports with currency payments of principal and interest. Recycling of funds related to the oil and gas sector has partly been carried out by the state and by the sovereign funds controlled by the state. Revenue from export duties has been accumulated in the funds and applied in accordance with the funds? investment strategies. Chapter 7 is based on the presentation by Zuzana Fungácová, BOFIT, Bank of Finland ?Risk-taking by Russian banks: do location, ownership and size matter?? The paper is co-authored by Laura Solanko. The rapid growth of the assets of Russian banks has in the last 6?7 years contributed to a decrease in the capital adequacy ratio, thus influencing the ability of banks to cope with risk. In the paper, the authors investigate the relationship between bank characteristics and risk-taking. The banks are divided into different subgroups by size, ownership and location. The authors distinguish between state-controlled, foreign-controlled and domestic private banks. Risk is measured in two different ways: By group-wise comparisons of financial risk ratios i.e. accounting data, and by regression analysis of bank insolvency risk as measured by a Z-score indicator. The average level of financial ratios are all well above the regulatory minima set by Central Bank of Russia. Large banks in Russia have higher insolvency risk than small ones. Foreign-owned banks exhibit higher insolvency risk than domestic banks. State-controlled banks are on average more stable than the private domestic banks. Similar to the case of foreign banks, large state-controlled banks are more stable than the others. Regional banks are significantly more prone to risk-taking than their counterparts in Moscow. Chapter 8 is based on the keynote speech ?Russia?s Financial Crisis: Causes, Consequences, and Prospects? by Zeljko Bogetic, World Bank, Moscow. Until mid-2008, Russia was viewed as a ?safe haven? during turbulent times in global financial markets. Record high oil prices, strong macroeconomic fundamentals, lack of exposure of Russian banks to the US sub-prime mortgage markets, strong ratings and a strong appreciating currency explained the confidence in Russia. After mid-2008 Russia was hit. There was an oil price shock, a sudden stop in capital flows, and a sharp tightening of external borrowing conditions. The paper contains a diagram that documents an almost perfect correlation of the Russian stock index RTS with the price of oil. From the peaks in May-June 2008 to the end of the year, the RTS moved from 2400 to 440 and the oil price from USD 144 per barrel to USD 45 per barrel. The non-oil external current account deficit continued to deteriorate very fast in 2008 as import volumes grew faster than non-oil exports. Incoming FDIs declined and worsened the composition of capital flows towards borrowing. While public external debt remained moderate, private (corporate and bank) debt grew rapidly. In the balance sheets of Russian banks, the loan-deposit ratio increased from approximately 107% in 2005 to 127% in the autumn of 2008, making the banking sector more exposed to the interbank market and to rollover risk. As response to the crisis, the Russian authorities have loosened their monetary stance and provided fiscal support to ease the liquidity crisis. The exchange rate has continuously been managed with progressive widening of the bi-currency corridor. After a gradual depreciation since November 2008, the rouble was devalued in mid January 2009. The speaker described the 2009 outlook for the Russian economy as very uncertain. It is likely that the twin surpluses on the Government budget and the balance of payments current account will disappear, but thanks to the prudent macroeconomic policies in recent years, these deficits can be financed for some time. The speaker reflected on the social impact of the crisis. If the recession in 2009 becomes deeper, it might require an introduction of a fiscal stimulus package focusing on domestic demand and the poorer segments of the population, including strengthening of the unemployment, training and social assistance and possibly well designed public works. Chapter 9 is based on the presentation by Peter Havlik, The Vienna Institute for International Economic Studies (WIIW) ?Russian Economy and the Global Turmoil.? The paper contains very illustrative exhibits that show the development of Russian GDP, exports, imports, inflation, money supply, stock prices and nominal and real exchange rates. Among the Putin administration?s key achievements, he lists improved living standards, rising employment, more FDI inflows, repayment of external debt, ballooning foreign exchange reserves, restoring stability, stronger role of the state but also deteriorating external relations. Despite strong economic fundamentals, Russia has been seriously hit by the global crisis. The Medvedev administration faces serious challenges. It plans to use industrial policy instruments in order to reduce the dependence on energy proceeds. The Government offers targeted support to various public-private partnership projects in the automotive, aviation, shipbuilding and selected high-tech industries. According to the speaker, some of the envisaged industrial policy tools could well be in conflict with WTO rules and make Russia?s WTO accession more difficult. Chapter 10 is based on the workshop contribution by Debora Revoltella, UniCredit Group ?The Russian Banking Sector: What to Expect? The paper is co-authored by Vladimir V.Osakovsky and Valery Invushin. It is divided in three sections: 1) The past: Russian economic renaissance, 2) The crisis: Politics and Economics join forces, and 3) Longer term prospects are brighter. Up to 2008, Russia enjoyed strong growth in domestic investment, consumption and GDP. Prudent fiscal policy and massive capital inflows helped to amass the world?s third largest international reserves. The country was, however, exposed to global commodities prices, a demographic crisis, a rigid labour market and an increasing dependence on foreign sources of funding. The crisis in 2008 was triggered by collapse of global commodities prices, massive capital flight, failures of some large market participants and general loss of confidence abroad and at home. As reaction to the challenges posed by the crisis, the Government and Central bank of Russia initiated corporate debt refinancing assistance, liquidity infusion into the banking system and fiscal stimuli. The authors expect a major restructuring of the Russian banking sector including a considerable reduction of the number of financial institutions.
Keywords: E5; O5; P2; Q43; 330; Russia; rouble; oil price; banking; transition economics; global financial crisis; Central Bank of Russia; Finanzsektor; Russland